Design, Analysis, and Measurements of an Antenna Structure for 2.4 GHz Wireless Applications. (3rd November 2010) - Votis, Constantinos I.; Kostarakis, Panos; Alexandridis, Antonis A.
Abstract : This paper reports measured results of a multielement antenna implementation, we constructed, that performs at 2.4 GHz ISM band. Particular emphasis was given to the scattering parameters and validation characterization of this antenna structure. The constructed multielement antenna that was studied in both azimuth and elevation planes consists of a number of printed dipoles with integrated baluns. Due to its multielement construction, the proposed antenna structure is suitable for applications that require multielements nature such as MIMO, channel sounder, and digital beamforming.